State-Owned Islamic Banks Merger Impact on Capital Quality and Market Share of National Islamic Banking - Farhan Lauda; Yeti Lis Purnamadewi; Irfan Syauqi Beik (AFRE (Accounting and Financial Review), 2024)
This study aims to analyze the impact of the merger of three state-owned Islamic banks on the capital quality and market share of national Islamic banking and identify the factors influencing them. The research employs a quantitative approach using monthly time series data from 2018 to 2023. Data analysis was conducted using a paired sample t-test, Wilcoxon Sign-Test and Vector Error Correction Model (VECM). The results show significant difference in the market share of national Islamic banking before and after the merger, though there was no significant difference in the average of CAR. VECM analysis reveals that NPF, ROE, BOPO, and FDR influence CAR and market share of Islamic banking in the long term, while FDR has a significant effect on CAR in the short term. The merger significantly affects CAR but not the market share of Islamic banking, whereas controlling shareholders (PSP) decisions significantly impact market share of Islamic banking. JEL Classification: C14, G21, G28 DOI: https://doi.org/10.26905/afr.v7i3.14433